Capacity Benefit Analysis of Pumped-storage Power Stations in a New-type Power System - ZHANG Xiangcheng; TIAN Xu; ZHANG Guihong; LIU Fei; FAN Hengjian; LI Zhiyi (Journal of Harbin University of Science and Technology)
The investment and construction of pumpedstorage power stations will bring multiple benefits to the safe and reliable operation of the new power system, and capacity benefits are the basic guarantee for maintaining the balance of power supply and demand.However, at this stage, the capacity benefits of pumped storage power plants are not fully recognized and compensated, resulting in unsatisfactory profitability and poor enthusiasm for investment and construction.To promote the development of pumpedstorage power plants in the process of energy to power transition, this paper proposes a capacity benefit evaluation method for pumped storage power stations based on the concept of production and operation simulation; a pumped storage power station is established.The joint optimization operation model of energy power station and wind, light, water, fire and other types of power sources is established. Based on the operating data of a certain province’s power system, it is verified that the pumped storage power station can reduce the installed capacity of thermal power plants and reduce renewable energy sources, thereby laying the theoretical foundation for analyzing the role of pumped storage power stations in the transition of power and energy industry.